Perception among undergraduate medical students towards health research methodology & publications in a tertiary care hospital of Assam (Panacea Journal of Medical Sciences, 2022)
Introduction: Research experience gained by medical students during their under graduate tenure plays a significant role in their future endeavours in the field of medical research. The aim of the present study was to assess the level of knowledge about attitudes regarding biomedical health research and publications among medical students.Materials and Methods : A cross-sectional descriptive study was conducted and randomly selected among 200 undergraduate medical college students of Tezpur Medical College, Tezpur, Assam in 2018 to access the knowledge about their attitudes on health research and scientific publications. A prefix pretested proforma was employed to assess the knowledge and attitudes of the students. Informed consent was duly taken. The data thus obtained was then analyzed using MS Excel.Results : Among the 200 study participants, only 70(35%) students feel confident in interpreting and writing a research paper, and 135(67.5%) students feel lack of their knowledge on research methodology and is the cause of less publication & research, while 102(51%) and 120(60%) says lack of senior’s knowledge and mentors respectability is the cause of less publication. Interestingly only 5(2.5%) participants had published in journals and 195(97.5%) says that they were never written any scientific paper. Majority of students 174(87%) had not participated in a research project (apart from mandatory academic projects). A good number students do feel that lack of funds and facilities, and mentorship are important causes of no publication and research in medical colleges.Conclusion: Medical colleges should emphasize more on health research among the undergraduate students. There is a need to reform the medical curriculum with more weightage towards research methodology awareness, workshops and plannings in order toimprove the situation in the field of medical education and research.